Common Carotid Artery Occlusion and Double-Nucleated Cellular Structures In The Rat Sensorimotor Cerebral Cortex - D. B. Avdeev; V. A. Akulinin; S. S. Stepanov; A. Yu. Shoronova; L. M. Makarieva; A. V. Gorbunova; M. S. Korzhuk; M. V. Markelov (Общая реаниматология, 2021)
The aim of the study. To study the double-nucleated cellular structures of the brain sensorimotor cortex (SMC) of sexually mature white rats after a 40-minute occlusion of the common carotid arteries.Methods. Acute ischemia was simulated in white Wistar rats by 40-minute occlusion of the common carotid arteries (OCCA). We performed comparative morphometric evaluation of cyto-, dendro-, synapto-, and glioar-chitectonics of the neocortex in intact animals (n=5), and 1 (n=5), 3 (n=5), and 7 days (n=5) after OCCA. We used Nissl, hematoxylin and eosin staining, and immunohistochemical reactions for NSE, MAP-2, HSP-70, p38, caspase-3, GFAP, AIF1, and Ki-67. Numerical density of pyramidal neurons, oligodendrocytes (ODCs), mi-croglyocytes (MGCs), presence of dystrophic and necrobiotic neurons with one or more nucleoli, hetero- and dikaryons were assessed. Statistical hypotheses were tested using Statistica 8.0 software.Results. The percentage of dystrophic and necrobiotic neurons, nerve cells with two nuclei or two or more nucleoli, the total number (proliferation) and percentage of hypertrophic astrocytes, ODCs and MGCs increased significantly after OCCA. The total numerical density of SMC neurons decreased by 26.4% (P=0.001) in layer III and by 18.5% in layer V (Mann-Whitney U Test; P=0.01) after OCCA throughout the observation period. Pathological and compensatory changes were diffusely focal and more pronounced in layer III of the neocortex. The density of bi-nucleated heterokaryons and dikaryons remained unchanged on days 1 and 3 after OCCA vs control and was 3.5 (1.5-4.0)/mm2, and increased to 6.5 (5.0-8.5)/mm2 on day 7 (Mann-Whitney U Test; P=0.002). This increase occurred along with a higher density of ODCs and MGCs than in the control. The maximum number of neurons with two or more nucleoli was also noted in layer III and V during this period.Conclusion. After 40-minute OCCA in SMC, parallel to the dystrophic and necrobiotic changes of pyramidal neurons and activation of neuroglial cells, there was an increase in the formation of heterokaryons and neurons with amplified nucleolus. These changes were considered as a variant of neuronal response to ischemic damage.